Building Competitive Advantage Through Trust, Innovation, and Customer Loyalty in E-Business - Keni Kaniawati; Andhi Sukma; Desy Oktaviani (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The growth of Indonesia’s e-commerce industry has created intense competition, requiring businesses to strengthen their competitive advantage through effective digital strategies. Trust, innovation, and customer loyalty are considered key drivers of digital competitiveness, yet firms still face challenges in sustaining loyalty and digital performance.Purpose: This study aims to examine the effects of trust, innovation, and customer loyalty on competitive advantage and their subsequent influence on fundamental e-business performance.Design/methodology/approach: A quantitative research approach was employed, utilizing structured questionnaires distributed to 220 respondents who actively use e-commerce platforms, including Shopee, Tokopedia, Lazada, Blibli, and Bukalapak. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0.Findings/Result: The results indicate that customer loyalty is the strongest predictor of competitive advantage, while trust has a significant impact on fundamental e-business practices. However, innovation did not have a significant direct effect. Competitive advantage was also found to mediate the relationship between customer loyalty and e-business performance.Conclusion: Strengthening customer loyalty and building trust are crucial strategies for enhancing competitiveness and digital business success. To achieve this, innovation must be more closely integrated with customer needs to deliver value.Originality/value (state of the art): This study contributes to the literature by integrating behavioral and strategic constructs into a unified model, offering new insights into the role of intangible assets in enhancing e-commerce performance in emerging markets, such as Indonesia. Keywords:  competitive advantage, customer loyalty, digital performance, innovation, e-business